2022
DOI: 10.3389/fcell.2022.903781
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Sensing Pathways in DNA Repair Targeted Cancer Therapy

Abstract: The repair of DNA damage is a complex process, which helps to maintain genome fidelity, and the ability of cancer cells to repair therapeutically DNA damage induced by clinical treatments will affect the therapeutic efficacy. In the past decade, great success has been achieved by targeting the DNA repair network in tumors. Recent studies suggest that DNA damage impacts cellular innate and adaptive immune responses through nucleic acid-sensing pathways, which play essential roles in the efficacy of DNA repair t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 193 publications
(200 reference statements)
0
6
0
Order By: Relevance
“…Moderate activation of PARP promotes cell survival through a repair mechanism [17,19]. PARP is a factor with nuclear expression, and counter-marking with DAPI identifies the cells with viable nuclei [19,35,37]. In this context, the project aims to: histopathological and immunofluorescence assessment of skin toxicity of the 2-chloroethyl-ethyl sulphide (CEES) vesicant in order to develop a complex antidotic formulation that pharmacodynamically antagonizes the toxicity of this category of blistering agents.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate activation of PARP promotes cell survival through a repair mechanism [17,19]. PARP is a factor with nuclear expression, and counter-marking with DAPI identifies the cells with viable nuclei [19,35,37]. In this context, the project aims to: histopathological and immunofluorescence assessment of skin toxicity of the 2-chloroethyl-ethyl sulphide (CEES) vesicant in order to develop a complex antidotic formulation that pharmacodynamically antagonizes the toxicity of this category of blistering agents.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, cytoplasmic mtDNA significantly triggered STING signalling, as evidenced by phosphorylation of TBK1‐IRF3 and the promotion of type I IFNs transcription. Previous studies have indicated that mtDNA serves as an endogenous TLR9 agonist, thus involved in the development of certain disease and circulating mtDNA has a positive correlation with increased inflammatory phenotypes, as well as nuclear DNA 36,37 . However, it is difficult to determine the relative contribution of circulating nuclear DNA or mtDNA to inflammatory pathology in many cases, thus further investigations are warranted 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that mtDNA serves as an endogenous TLR9 agonist, thus involved in the development of certain disease and circulating mtDNA has a positive correlation with increased inflammatory phenotypes, as well as nuclear DNA. 36,37 However, it is difficult to determine the relative contribution of circulating nuclear DNA or mtDNA to inflammatory pathology in many cases, thus further investigations are warranted. 27 Our results suggested that cytoplasmic mtDNA up-regulated p65 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear ALRs attach to chromatin, preventing DNA repair machinery from reaching the damaged location and encouraging self-oligomerization, which compacts the chromatin [ 144 ]. ALRs may be a therapeutic target for illnesses caused by DNA damage because they may interact more directly than other DNA sensors with DDR components, particularly in the nucleus [ 145 ]. Additionally, by activating caspase 1 and cleaving pro-IL-1β and pro-IL-18 to generate IL-1β and IL-18, respectively, ATM and DNA-PKcs support AIM2 inflammasome activation [ 146 , 147 ].…”
Section: The Regulation Of Innate Immune Sensors By Ddr Componentsmentioning
confidence: 99%
“…In particular, Ku70 translocates into the cytoplasm, where it senses DNA from cytosolic viruses to trigger the production of IFN-λ1, a Type-III IFN that IRF-1 and IRF-7 mediate against viral infection [ 91 , 117 , 118 ]. It has been proposed that STING functions as a downstream adaptor for the Ku complex, which phosphorylates IRF3 to trigger IFN transcription [ 117 , 145 ]. Interestingly, DNA-PK stimulates IFN-β production through the SIDSp pathway, which is independent of STING.…”
Section: The Regulation Of Innate Immune Sensors By Ddr Componentsmentioning
confidence: 99%